Germanic and Slavic paganisms: security threats and resiliency - Aitamurto, Kaarina; Downing, Ross (Religion at the boundaries, 2025)
This volume offers a novel and timely examination of the complexities of contemporary Slavic and Germanic paganisms, and their dual potential for both far-right, ethno-purist and nationalistic social movements as well as inspiring inclusive visions for social and ecological renewal. Chapters aim to bridge the information silos often found between academia, governmental institutions and pagan communities, providing a rich resource for all parties